Diversifying academic medicine: One search committee at a time - Jacobs, N. Nicole; Esquierdo-Leal, Jovonnie; Smith, Gregory S.; Piasecki, Melissa; Houmanfar, Ramona A. (Frontiers in Public Health, 2022)
Despite increasing attention to lack of diversity among medical education faculty, those traditionally underrepresented in medicine remain so. In 2017, the University of Nevada, Reno School of Medicine approved a new policy to increase diversity in the faculty search process, which includes a mandatory 2-h workshop on best practices in search processes and implicit bias training. Workshop participants were 179 search committee members making up 55 committees from February 2017 to March 2020. Participants completed two separate social validity surveys, one immediately following the workshop and another following the close of their search, and rated various aspects of the workshop. Each search committee completed a Diversity Checklist (DCL) of various mandatory and best practices to be implemented during each search. Historical data on diversity of job applicants, interviewees, and hires over the 5-year period immediately preceding workshop implementation were compared with corresponding diversity data from the participant search committees for a 3-year period following implementation of the workshop. Social validity surveys indicated high ratings pertaining to the benefits of the workshop (means 3.82–4.39 out of 5). Implementation of practices outlined in the DCL were high (94% of mandatory and 87% of best practices). Chi-square analyses of diversity data before and after implementation revealed significant increases in overall diversity (both race and gender) of applicants (p < 0.001), interviewees (p = 0.002), and those offered a position (p = 0.002), in the time period following implementation. Follow-up comparisons found greater increases for gender relative to race/ethnicity.